Fish behavior. - Bruslé, Jacques (John Wiley & Sons, Incorporated, 2020)
Advances in underwater exploration, in situ observation of fish populations, as well as the development of cutting-edge technologies, provide modern insights into behaviors and strategies of fish, whose cognitive abilities have long been underestimated and undervalued. Fish Behavior 2 presents current knowledge about fish biology, ecology and ethology. In light of the most recent scientific work, this book examines topics such as their reproductive behavior and the expression of their personalities. It also addresses issues associated with neurophysiological conditioning of behaviors, in relation to the structural and functional complexity of their brains. This book is intended for researchers, teachers, master's and doctoral students in biology and biogeography, engineers and technicians responsible for the development and protection of natural environments and public aquariums, in addition to aquaculturists, fishermen, environmentalists and ecologists.--Provided by publisher.